16 The burden of cancer overdiagnosis in australia. (4th December 2019) - Glasziou, Paul; Jones, Mark; Pathirana, Thanya; Barratt, Alexandra; Bell, Katy
Abstract : Background and objectives: Burden of cancer is increasing worldwide, and in Australia, partly due to overdiagnosis: cancers which would never cause symptoms or harm if left undetected. We sought to estimate the current burden of overdiagnosis of cancer in Australia. Design, setting, and outcomes: We calculated and compared current (2012) and past (1982) lifetime risks of cancer for 5 cancers: prostate, breast, renal, thyroid cancers and melanoma. Using routinely collected Australia-wide data on cancer specific incidence and mortality, we used the Devcan software to estimate the probability of cancer specific diagnosis for each age group adjusted for the competing risk of dying from other causes. To account for increases in breast cancer and melanoma from changes in risk factors over time, we adjusted the lifetime risk of these cancers in 1982 upwards. To estimate the overall overdiagnosis we multiplied each cancer's estimated overdiagnosis by its incidence and summed these. For breast cancers and melanoma, we did sensitivity analyses excluding in-situ cancers. Results: For Australian women, the lifetime probability of being diagnosed with one of four cancers increased by 10.1% in total, made up of 3.4%, 0.6%, 1% and 5.1% increases for breast, renal, thyroid cancer and melanoma, respectively. When we restricted analysis to invasive cancers, the lifetime probability for breast cancer and melanoma increased by 1.7% and 0.7%, respectively. We estimated that 22% of breast cancers (13% of invasive breast cancers), 58% of renal cancers, 73% of thyroid cancers and 54% of melanomas (15% of invasive melanomas) were overdiagnosed in 2012. Overdiagnosis of these cancers accounted for 18% of all cancers (8% of all invasive cancers) in Australian women in 2012. For Australian men, the lifetime probability of being diagnosed with one of four cancers increased by 17.4% in total, made up of 8.2%, 0.8%, 0.4% and 8% for prostate, renal, thyroid cancer and melanoma, respectively. When we restricted analysis to invasive cancers, the lifetime probability for melanoma increased by 1.5%. We estimated that 42% of prostate cancers, 42% of renal cancers, 73% of thyroid cancers and 58% of melanomas (22% of invasive melanomas) were overdiagnosed in 2012. Overdiagnosis of these cancers accounted for 24% of all cancers (16% of all invasive cancers) in Australian men in 2012. Conclusions: For Australia, these estimates mean that over 11, 000 cancers in women, and 18, 000 cancers in men are currently overdiagnosed each year.). Health policies are urgently needed to reduce the current rates of overdiagnosis. Further, health services need to be alert to the potential for new areas of overdiagnosis to arise and monitor to detect these early.